In vitro susceptibilities of mycoplasmas and ureaplasmas to new macrolides and aryl-fluoroquinolones. - Waites, K B (1988)
In vitro activities of the new macrolides clarithromycin, previously designated A-56268 (TE-031), and A-63075 and of the aryl-fluoroquinolones difloxacin (A-56619) and temafloxacin (A-62254) against 14 strains of Mycoplasma pneumoniae, 20 strains of Mycoplasma hominis, and 28 strains of Ureaplasma urealyticum were compared with that of erythromycin. All three macrolides inhibited growth of M. pneumoniae at less than 0.125 micrograms/ml. No macrolide was active against M. hominis. For five strains of U. urealyticum, MICs were greater than 256 micrograms/ml for all 3 macrolides. Excluding these, no other strain of U. urealyticum had an initial MIC of clarithromycin of greater than 1 microgram/ml, while five had initial MICs of erythromycin which were greater than 4 micrograms/ml. A-63075 was the least active of the three macrolides against ureaplasmas. Temafloxacin and difloxacin had similar activities against all three species, initially inhibiting 90% of M. pneumoniae strains at 2 and 8 micrograms/ml, 90% of M. hominis strains at 2 and 4 micrograms/ml, and 90% of U. urealyticum strains at 4 and 8 micrograms/ml, respectively. Additional pharmacokinetic and clinical trials with the new macrolides and quinolones with mycoplasmal or ureaplasmal infections are indicated.